Cognitive decline tracks motor progression and not disease duration in Parkinson patients - BD Riggeal (Dove Medical Press, 2007)
BD Riggeal1, GP Crucian1, P Seignourel2, CE Jacobson IV1, MS Okun1, RL Rodriguez1, Hubert H Fernandez11Department of Neurology; 2Department of Community Health and Psychology, University of Florida, Gainesville, FL, USAAbstract: We performed an analysis of prospectively-acquired cross sectional data on 106 Parkinson disease (PD) patients who underwent comprehensive neuropsychological testing and the Unified Parkinson Disease Rating Scale (UPDRS) motor scale. A significant correlation between the UPDRS motor and neuropsychological tests in all cognitive domains except for general intelligence and visuo-spatial function was seen. In this study, cognitive decline within this PD cohort correlated with motor impairment but not disease duration. Our findings suggest that overall cognitive impairment (except visuospatial dysfunction) may track motor progression in PD more than duration of disease. Longitudinal studies are needed to confirm our results.Keywords: Parkinson, dementia, cognition, visual-spatial dysfunction